Childhood Health Shocks, Comparative Advantage, and Long-Term Outcomes: Evidence from the Last Danish Polio Epidemic - Gensowski, Miriam; Torben Heien Nielsen; Nete Munk Nielsen; Rossin-Slater, Maya; Wüst, Miriam (NBER Working Paper Series, 2018)
Working Paper No. 24753 A large literature documents that childhood health shocks have lasting negative consequences for adult outcomes. This paper demonstrates that the adversity of childhood physical disability can be mediated by individuals' educational and occupational choices, which reflect their comparative advantage. We merge records on children hospitalized with poliomyelitis during the 1952 Danish epidemic to census and administrative data, and exploit quasi-random variation in paralysis incidence. While childhood disability increases the likelihood of early retirement and disability pension receipt at age 50, paralytic polio survivors obtain higher education and are more likely to work in white-collar and computer-demanding jobs than their non-paralytic counterparts.